2010
DOI: 10.1002/mas.20270
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics in investigation of protein nitration in kidney disease: Technical challenges and perspectives from the spontaneously hypertensive rat

Abstract: Kidneys are the mammalian organs with widest range of oxidative status ranging from the well-perfused cortex to the relatively anoxic medulla. This organ is of key interest from the perspective of hypertension, an important contributor to human mortality, and there has been growing use of the spontaneously hypertensive rat (SHR) as a model to explore oxidative stress in hypertensive kidney. Nitrosative stress is often associated with oxidative stress and, like oxidative stress, can lead to covalent modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 145 publications
(175 reference statements)
0
19
0
Order By: Relevance
“…Their formation may interfere with functional and signaling aspects of targeted residues, for instance, hampering the phosphorylation of Tyr residues of signaling proteins. 64 Conditions of nitrosative stress investigated in vivo in a flavohemoglobin mutant of S. cerevisiae, have revealed that 3NT may form on the mitochondrial proteins Aco and IDH, suggesting specific targeting of the citric acid cycle by RNS. 65 Accordingly, during nitrosative stress of the fungal pathogen Cryptococcus neoformans, Aco and other metabolic genes were found to be up-regulated as well as classical stress genes such as thiol peroxidase and gluthatione reductase, 66 thus suggesting a role for NO-induced PTMs in the response that coordinates different groups of genes involved in repair and adaptation with energy supply genes.…”
Section: Cytosolic Aconitase: a Link Between Ros Metabolism And Iron mentioning
confidence: 99%
“…Their formation may interfere with functional and signaling aspects of targeted residues, for instance, hampering the phosphorylation of Tyr residues of signaling proteins. 64 Conditions of nitrosative stress investigated in vivo in a flavohemoglobin mutant of S. cerevisiae, have revealed that 3NT may form on the mitochondrial proteins Aco and IDH, suggesting specific targeting of the citric acid cycle by RNS. 65 Accordingly, during nitrosative stress of the fungal pathogen Cryptococcus neoformans, Aco and other metabolic genes were found to be up-regulated as well as classical stress genes such as thiol peroxidase and gluthatione reductase, 66 thus suggesting a role for NO-induced PTMs in the response that coordinates different groups of genes involved in repair and adaptation with energy supply genes.…”
Section: Cytosolic Aconitase: a Link Between Ros Metabolism And Iron mentioning
confidence: 99%
“…Nitration of tyrosine amino acids is considered a signature of excessive ONOO − and/or NO generation, however the subset of Tyrosine residues available for nitration is generally considered to be low and consequently the number of proteins detected to be nitrated (Tyther et al, 2011; Batthyany et al, 2017). Interest in Tyrosine nitration in particular is due to the role of Tyrosine in phosphorylation/dephosphorylation signaling.…”
Section: Tyrosine Nitrationmentioning
confidence: 99%
“…In studies of this type, kidney is consistently one of the largest contributors of plasma proteins (40). Another category of redox modification found in proteins ( T1 c Table 1) is nitration, in particular, modification of tyrosine to 3-nitrotyrosine (73,76). Increased 3-nitrotyrosine in both chronic and end-stage kidney disease patients was found in serum proteins by both immunoblotting and LC-tandem MS (57).…”
Section: Redox Proteomics In Hypertension Studymentioning
confidence: 99%